Does it pay to have friends? Social ties and executive appointments in banking - Allen N. Berger; Thomas Kick; Michael Koetter; Klaus Schaeck (Deutsche Bundesbank, 2011)
Social capital theory predicts individuals establish social ties based on homophily, i.e., affinities for similar others. We exploit a unique sample to analyze how similarities and social ties affect career outcomes in banking based on age, education, gender, and employment history to examine if homophily and connectedness increase the probability that the appointee to an executive board is an outsider (an individual without previous employment at the bank) compared to being an insider. Our results show that homophily based on age and gender raises the chance of the successful candidate being an outsider, whereas similar educational backgrounds reduce the chance that the appointee comes from outside. When we examine performance effects, we find weak evidence that social ties are associated with reduced profitability.
Keywords: G21; G32; G34; J16; 330; Social networks; executive careers; banking; corporate governance